Qualitative and Quantitative Modeling of the Artificial Citizens using Genetic Methods - Muhammad Salman; Hajra Klair (Institute of Advanced Engineering and Science, 2015)
Human Development Index is a key indicator of a country’s development as formulated by the United Nation. It determines a country’s progress in three main areas: Life Expectancy, Education and Income. A number of researches have been made for the understanding of how the different factors that together make up the Human development Index are correlated and to what extent each of them affects the HDI value. However, there are always certain unpredictable events that directly or indirectly affect the Human Development Index. Our project aims to incorporate the interdependencies between different factors of the HDI with the simulation of random events in an artificial population to establish the HDI value. This value is future forecasting as the HDI value output would be based upon the input values given by the user, including a certain number of years after which HDI is to be determined. The user would also have other options available to him which he can use to determine the HDI value. That is, after changing the values of various different factors upon which HDI depends by his own choice, the user can effectively study different elements affecting HDI. This can prove to be a great convenience in policy making. Genetic Algorithm is a technique that mimics the process of natural evolution. The essence of Genetic Algorithm is being employed in this system to generate artificial agents for Pakistan’s entire population. This population (represented as chromosomes of bit strings) would then undergo various genetic operations like fitness evaluation, cross-over and mutation. Then after certain generations of the initial population have evolved after a specific number of years as input by the user, the Human Development Index value would be calculated. This value would be determined from the statistical analysis of the population. This analysis has been encoded in the system and is result of extensive study of various research articles and books that facilitate in understanding how socio-economic parameters affect each other and the HDI.